Uso medicinal da pimenta malagueta (Capsicum frutescens L.) em uma comunidade de várzea à margem do rio Amazonas, Santarém, Pará, Brasil - ROMAN, André Luís Cote (Universidade Federal do Pará, 2017)
An ethnobotanical study was carried out for this study aimed at understanding the medicinal importance of malagueta / chili pepper (C. frutescens L.) in the daily life of the people of Cabeça D'Onça, an area in the Amazon River floodplain. The community of approximately 330 residents is situated in the municipality of Santarém, Pará State. In total, 116 people from 70 households were interviewed for this work. Information regarding the medicinal uses of these peppers was collected in semi-structured interviews and compiled in detail. In the second phase of the study, structured interviews were carried out in 40 households with 80 people (40 couples) to determine the most commonly-known uses of the peppers in the study area. Over 50% of those interviewed cited the use of the malagueta in curing certain illnesses reputed to be caused by contact with water from the Amazon River, including 'pano-branco', and 'impinge' (both diseases of the skin treated with the leaves) and rheumatism (treated with the fruit). A comparison of the data obtained in this study with published literature reveals strong indigenous influence in their medicinal use.